A five year financial plan for Tao Commodity Trader Incorporated - Bete, Evalynne Mae D. 4 0 16; 5 (2016)
EXECUTIVE SUMMARY: Tao Commodity Trader Incorporated is one of the leading molasses traders in the country capturing 35% of the market share. They venture into buying, selling, and distributing molasses among large companies distilleries in the country. Tao Commodity Trader, Inc. is wholly owned subsidiary of Tao Corporation, engaging in supply-chain of commodities and services, gaining spot on the Top 500 Corporations in the Philippines. Tao Corporation humbly started as Tao Community, and after over 20 years, has evolved into large group of companies with diverse specialties such as wellness, research, commodities, science and technology. Tao Commodity is also one of the major contributors of Taos Puso Foundation servicing over 100,000 farmers in Negros, Davao, Dumaguete etc. Despite of its promising position in sugarcane and molasses industry, the entity faces a problem with its working capital management. The entity's problem in working capital management has branched even more to illiquidity characterized bu low cash balance and insufficient current assets, and to solvency forcing the company to incur large amount of debts to support their operations. The entity's inefficient working capital management is caused by poor cash inflow generated from sales, slow turnover of inventories and having too little amount of cash and cash equivalents. Molasses, as a by-product of sugar, is deemed price elastic. That is, a movement in price will not render fall on a demand, or with an insignificant decrease on demand. Given, it is not a product for end-consumer, companies, especially distilleries, are in constant need of molasses as one major ingredient for beer, wine and other alcoholic drinks. This plan is proposed to improve the entity's working capital management. This is for the purpose of solving the entity's working capital management, alongside with its specific-problems.
Research Paper: (BSBA major in Finance and Treasury Management)- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2